H2‐Fueled ATP Synthesis on an Electrode: Mimicking Cellular Respiration. Issue 21 (15th March 2016) - Gutiérrez‐Sanz, Óscar; Natale, Paolo; Márquez, Ileana; Marques, Marta C.; Zacarias, Sonia; Pita, Marcos; Pereira, Inês A. C.; López‐Montero, Iván; De Lacey, Antonio L.; Vélez, Marisela
Abstract: ATP, the molecule used by living organisms to supply energy to many different metabolic processes, is synthesized mostly by the ATPase synthase using a proton or sodium gradient generated across a lipid membrane. We present evidence that a modified electrode surface integrating a NiFeSe hydrogenase and a F1 F0 ‐ATPase in a lipid membrane can couple the electrochemical oxidation of H2 to the synthesis of ATP. This electrode‐assisted conversion of H2 gas into ATP could serve to generate this biochemical fuel locally when required in biomedical devices or enzymatic synthesis of valuable products. Abstract : ATP synthesis fueled by H2 : A gold electrode modified with an oriented membrane‐bound NiFeSe hydrogenase, a lipid membrane, and an integrated F1 F0 ‐ATPase generates a local proton gradient by electroenzymatic H2 oxidation, which is then used to synthesize ATP. This electrode‐assisted conversion of H2 into ATP could locally generate biochemical fuel in medical devices or enzymatic synthesis.